Review of “Chinese Translations of Western Images: A Study of Christian Imagery in Sixteenth- and Seventeenth-Century China” - XU, Yi (Journal of Research for Christianity in China (JRCC), 2025)
Review of “Chinese Translations of Western Images: A Study of Christian Imagery in Sixteenth- and Seventeenth-Century China”